Association of Peripheral Lymphocyte and the Subset Levels With the Progression and Mortality of COVID-19: A Systematic Review and Meta-Analysis - Lu, Qun; Wang, Zhengyin; Yin, Yuan; Zhao, Yanrong; Tao, Ping; Zhong, Ping (Frontiers in Medicine, 2020)
Current evidences were controversial in the association between peripheral lymphocyte levels and the progression and mortality of Corona Virus Disease 2019 (COVID-19), and this meta-analysis aimed to clarify the association. A systematic search was conducted in public databases to identify all relevant studies, and study-specific odds ratio (OR) and 95% confidence intervals (CI) were pooled. Finally, 16 studies were identified with a total of 1873 progressive COVID-19 cases and 5177 stable COVID-19 cases. In COVID-19 progression, lymphocyte levels showed a significant negative correlation (OR: 0.68, 95% CI: 0.51-0.89), but it was not significant in the subsets of CD3+ T cells (OR: 0.97, 95% CI: 0.93-1.02), CD4+ T cells (OR: 0.93, 95% CI: 0.80-1.08), CD8+ T cells (OR: 0.96, 95% CI: 0.92-1.00), B cells (OR: 0.98, 95% CI: 0.92-1.04) or NK cells (OR: 0.80, 95% CI: 0.61-1.04). In COVID-19 mortality, lymphocyte levels showed a significant negative correlation (OR: 0.41, 95% CI: 0.20-0.85), but it was not significant in the subsets of CD3+ T cells (OR: 0.95, 95% CI: 0.86-1.05), CD4+ T cells (OR: 1.06, 95% CI: 0.86-1.31), CD8+ T cells (OR: 0.38, 95% CI: 0.14-1.01), B cells (OR: 0.98, 95% CI: 0.92-1.04) or NK cells (OR: 0.80, 95% CI: 0.61-1.04). In conclusion, current evidences suggested a significant negative association of peripheral lymphocyte levels with COVID-19 progression and mortality, but it was not significant in the subsets of CD3+ T cells, CD4+ T cells, CD8+ T cells, B cells and NK cells.